A phenomenological study of the lived experiences of partner relationship breakup during pregnancy: Psychosocial effects, coping mechanisms, and the healthcare providers' role - Abel Negussie; Abel Negussie; Eshetu Girma; Mirgissa Kaba (Frontiers Media S.A., 2023)
BackgroundPregnancy is a state of continuous changes in feelings and emotions, and highly stressful experiences such as a relationship breakup during this period may result in additional stress for the woman, making pregnancy and motherhood challenging. This study aimed to investigate pregnant women's lived experiences of partner relationship breakup during pregnancy, their coping mechanisms, and the role of healthcare providers in breakup cases during their Antenatal care visits.MethodsA phenomenological study approach was followed to seek an understanding of the lived experiences of pregnant women who encountered partner relationship breakup. The study was carried out in Hawassa, Ethiopia, and eight pregnant women were involved in in-depth interviews. The data meanings found from participants' experiences were described in a meaningful text and organized into themes. Key themes were developed in reference to the research objectives, and thematic analysis was used to analyze the data.ResultsPregnant women in such situations faced serious psychological and emotional distress, feelings of shame/embarrassment, prejudice and discrimination, and severe economic struggles. To cope with this multifaceted situation, pregnant women sought social support from family/relatives or close friends, and if they had no other options, from supporting organizations. The participants also revealed that they received no counseling from healthcare providers during their Antenatal care visits, and there was no further discussion to address their psychosocial problems.ConclusionsCommunity-level information, education, and communication should be initiated to aware communities about the psychosocial consequences of relationship breakup during pregnancy, address cultural norms and discrimination, and promote supportive environments. Women's empowerment activities and psychosocial support services should also be strengthened. In addition, the need for more comprehensive Antenatal care to address such unique risk conditions is indicated.